Early Determinants of Death Due to Multiple Organ Failure After Noncardiac Surgery in High-Risk Patients - Lobo, Suzana M. (2011)
BACKGROUND: Prediction of perioperative cardiac complications is important in the medical management of patients undergoing noncardiac surgery. However, these patients frequently die as a consequence of primary or secondary multiple organ failure (MOF), often as a result of sepsis. We investigated the early perioperative risk factors for in-hospital death due to MOF in surgical patients.METHODS: This was a prospective, multicenter, observational cohort study performed in 21 Brazilian intensive care units (ICUs). Adult patients undergoing noncardiac surgery who were admitted to the ICU within 24 hours after operation were evaluated. MOF was characterized by the presence of at least 2 organ failures. To determine the relative risk (RR) of in-hospital death due to MOF, we performed a logistic regression multivariate analysis.RESULTS: A total of 587 patients were included (mean age, 62.4 +/- 17 years). ICU and hospital mortality rates were 15% and 20.6%, respectively. the main cause of death was MOF (53%). Peritonitis (RR 4.17, 95% confidence interval [CI] 1.38-12.6), diabetes (RR 3.63, 95% CI 1.17-11.2), unplanned surgery (RR 3.62, 95% CI 1.18-11.0), age (RR 1.04, 95% CI 1 0.01-1.08), and elevated serum lactate concentrations (RR 1.52, 95% CI 1.14-2.02), a high central venous pressure (RR 1.12, 95% CI 1.04-1.22), a fast heart rate (RR 3.63, 95% CI 1.17-11.2) and pH (RR 0.04, 95% CI 0.0005-0.38) on the day of admission were independent predictors of death due to MOF.CONCLUSIONS: MOF is the main cause of death after surgery in high-risk patients. Awareness of the risk factors for death due to MOF may be important in risk stratification and can suggest routes for therapy. (Anesth Analg 2011;112: 877-83)